2020
DOI: 10.3390/cancers12082300
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes-Mediated Transfer of Itga2 Promotes Migration and Invasion of Prostate Cancer Cells by Inducing Epithelial-Mesenchymal Transition

Abstract: Although integrin alpha 2 subunit (ITGA2) mediates cancer progression and metastasis, its transfer by exosomes has not been investigated in prostate cancer (PCa). We aimed to determine the role of exosomal ITGA2 derived from castration-resistant PCa (CRPC) cells in promoting aggressive phenotypes in androgen receptor (AR)-positive cells. Exosomes were co-incubated with recipient cells and tested for different cellular assays. ITGA2 was enriched in exosomes derived from CRPC cells. Co-culture of AR-positive cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…The expression of this mutant/ variant is decisive in determining the therapeutic approach for these patients [77] thus, determining EGFR status from exosomes instead of a tumor biopsy is of immense benefit for patients. Similar applications for exosomes have been described for ovarian cancer [73], melanoma [78] colorectal cancer [79], and prostate cancer [80,81]. Silva et al have reported that high levels of exosomes in plasma of patients with colorectal cancer were significantly associated with poorly differentiated tumors and with decreased overall survival (OS) [79] while patients with ovarian cancer exhibit significantly increased levels of serum exosomes compared to benign disease or healthy controls [73].…”
Section: Exosomesmentioning
confidence: 75%
“…The expression of this mutant/ variant is decisive in determining the therapeutic approach for these patients [77] thus, determining EGFR status from exosomes instead of a tumor biopsy is of immense benefit for patients. Similar applications for exosomes have been described for ovarian cancer [73], melanoma [78] colorectal cancer [79], and prostate cancer [80,81]. Silva et al have reported that high levels of exosomes in plasma of patients with colorectal cancer were significantly associated with poorly differentiated tumors and with decreased overall survival (OS) [79] while patients with ovarian cancer exhibit significantly increased levels of serum exosomes compared to benign disease or healthy controls [73].…”
Section: Exosomesmentioning
confidence: 75%
“…For example, they have been linked to the progression of such neurodegenerative diseases as Alzheimer’s [ 87 ] and Parkinson’s diseases [ 88 ]. In particular, exosomes have been shown to participate in various steps of malignancy: tumor growth [ 89 ], tumor angiogenesis [ 90 ], inhibition of immunity [ 91 ] and metastasis [ 92 ]. The horizontal transfer of biological information, via exosomes, between cancer cells or between cancer cells and stromal cells/distant cells facilitates the creation of a pro-tumorigenic microenvironment [ 89 , 92 , 93 , 94 ].…”
Section: Integrin Regulation In Exosomesmentioning
confidence: 99%
“…The inherence of integrins from cells to exosomes has an impact on the biological functions of cancer and immune cells ( Figure 2 ). Exosomal integrins participate in multiple steps of cancer progression: they increase cell adhesion and migration, guiding cancer exosomes to specific metastatic sites (metastatic organotropism), preparing pre-metastatic niche formation, modulating the angiogenic potential of endothelial cells and activating the expression of certain genes (e.g., Src and the pro-inflammatory and pro-migratory S100 gene) [ 92 , 101 , 102 ]. Integrins exposed on exosomes engage with their specific ligands on target cells, and this interaction constitutes an important factor in the internalization of exosomes.…”
Section: Integrin Regulation In Exosomesmentioning
confidence: 99%
See 2 more Smart Citations